Anticipatory cash for climate resilience - Balana, Bedru (International Food Policy Research Institute, 2023)
Bedru Balana, Research Fellow, IFPRI, presented these slides at the AAAE2023 Conference, Durban, South Africa, 18-21 September 2023. The authors acknowledged the contributions of CGIAR Initiative on National Policies and Strategies, Google, the International Rescue Committee, IFPRI, and USAID.